Serum immune complexes in systemic sclerosis: relationship with precipitating nuclear antibodies. Issue 2 (February 1985) - French, M A; Harrison, G; Penning, C A; Cunningham, J; Hughes, P; Rowell, N R
Abstract : In a comparative study of antinuclear antibodies (ANA) and immune complexes in the serum of 43 patients with systemic sclerosis (SS) ANA were detected by indirect immunofluorescence on Hep 2 cells and/or double immunodiffusion in 90% of patients, while immune complex assays were positive in 32% of patients. The immune complex assays were positive only in sera containing antibodies to Scl 70, n-RNP, Ro, and La. The presence of immune complexes in SS sera is therefore related to ANA specificity. This might explain the variable findings of several previous studies of immune complexes in SS.